1997
DOI: 10.1074/jbc.272.27.16807
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Symmetry and Sequence Context Dependence of the HIV-1 Proteinase Specificity

Abstract: Two major types of cleavage sites with different sequence preferences have been proposed for the human immunodeficiency virus type 1 (HIV-1) proteinase. To understand the nature of these sequence preferences better, single and multiple amino acid substitutions were introduced into a type 1 cleavage site peptide, thus changing it to a naturally occurring type 2 cleavage site sequence. Our results indicated that the previous classification of the retroviral cleavage sites may not be generally valid and that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 35 publications
4
20
0
Order By: Relevance
“…The HIV-1 PR recognizes at least seven substrate residues, from P4 to P3’ and each amino acid side chain of the substrate fits in successive subsites (S4 to S3′) formed by PR residues (Figure 5). Although the HIV-1 PR (similarly to the proteases of other retroviruses) is a symmetrical dimer of two identical subunits, the residues of naturally occurring cleavage sites do not show symmetrical arrangements (Figure 2) and no obvious symmetrical substrate preference has been observed for the specificity of HIV-1 PR [6]. Nevertheless, modeling showed that the same residues of the two enzyme subunits interact with the appropriate substrate residues at both sides of the scissile bond (Figure 5).…”
Section: Hiv-1 Proteasementioning
confidence: 99%
See 1 more Smart Citation
“…The HIV-1 PR recognizes at least seven substrate residues, from P4 to P3’ and each amino acid side chain of the substrate fits in successive subsites (S4 to S3′) formed by PR residues (Figure 5). Although the HIV-1 PR (similarly to the proteases of other retroviruses) is a symmetrical dimer of two identical subunits, the residues of naturally occurring cleavage sites do not show symmetrical arrangements (Figure 2) and no obvious symmetrical substrate preference has been observed for the specificity of HIV-1 PR [6]. Nevertheless, modeling showed that the same residues of the two enzyme subunits interact with the appropriate substrate residues at both sides of the scissile bond (Figure 5).…”
Section: Hiv-1 Proteasementioning
confidence: 99%
“…Nevertheless, based on similarities in amino acid sequences, primate lentiviral (HIV-1, HIV-2, SIV) cleavage sites were grouped into three classes [3], while analysis of a broader range of retroviral protease cleavage site sequences suggested two types of cleavage sites [4]. Later systematic specificity studies on HIV-1 PR also verified the existence of two types of cleavage sites, type 1 - having an aromatic residue and Pro - (highlighted in red in Figure 2), and type 2 having hydrophobic residues (excluding Pro) at the site of cleavage [5,6], defined as P1 and P1’ positions [7], respectively. These classical cleavage type sites also showed different preferences for the P2 and P2′ positions [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The best P2 residue (Ala) observed for AMV protease in the mapping study appears in the P2 position of its naturally occurring type 1 cleavage site sequence; however, the MPMV and MMTV sites contain the less favorable Ile and Thr, respectively, at this position (Table 2). In one of the MMLV cleavage sites, the most preferred Leu appears in P2, while the other contains a less preferred Ala. Discrepancies between the most preferred P2 residues and those observed in the naturally occurring cleavage sites might be due to the different sequence contexts, which have been shown to have a profound effect on the subsite preference of HIV-1 PR, including S2 (35), as well as to the possibility that not all retroviral cleavage sites are optimized evolutionarily for rapid processing (8).…”
Section: Downloaded Frommentioning
confidence: 99%
“…However, the difficulty is that the protease cleaves at different sites with little or no sequence similarities. In the last two decades, several studies, including wet-lab experiments on HIV-1 protease cleavage of oligopeptides, have been performed to study cleavage specificity [2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%